Graphene energy-saving lubricating oil special for corrosion flue gas environment fan and preparation method thereof

CN122941481APending Publication Date: 2026-10-20ZHONGRUN CHAOYOU (BEIJING) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611069188.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种腐蚀烟气环境风机专用石墨烯节能润滑油及其制备方法,该石墨烯节能润滑油解决了现有润滑油在腐蚀性烟气环境中抗腐蚀性差、易污染、易乳化、寿命短的技术难题

Benefits of technology

1、本发明的石墨烯节能润滑油包括石墨烯量子点复配改性添加剂和酸中和剂,其中,酸中和剂中和HCl时生成的盐类和水,通常情况下会破坏普通纳米材料的分散稳定性,但本发明所使用的石墨烯量子点复配改性添加剂中石墨烯量子点表面的丰富含氧、含氮官能团可有效吸附并稳定中和反应生成的极性产物,防止其团聚沉积,并且由于石墨烯量子点具有极高的比表面积,其官能团密度足以在换油周期内持续发挥作用。同时,石墨烯量子点形成的物理阻隔层减缓了HCl向金属表面的扩散速率,使酸中和剂得以“梯次消耗”,HCl加速试验后锈蚀等级达到最优的0级,且同等碱值储备下有效中和时间得以延长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of lubricating oil technology, and in particular to a graphene energy-saving lubricating oil for fans used in corrosive flue gas environments and its preparation method. The graphene energy-saving lubricating oil of this invention comprises the following components in parts by weight: 75-90 parts base oil, 2-6 parts extreme pressure anti-wear agent, 3-8 parts composite additive package, 1-5 parts graphene quantum dot compound modified additive, 1-3 parts detergent dispersant, 0.5-1.5 parts demulsifier, 0.2-1 part acid neutralizer, 0.1-0.5 parts friction modifier, and 0.2-0.8 parts antifoaming agent. This invention addresses the extreme operating conditions of PVC flue gas recovery fans, which involve the coexistence of "high-concentration HCl acidic gas + unpolymerized PVC dust + condensate". By using a specific combination and precise ratio of acid neutralizer, detergent dispersant, deemulsifier, extreme pressure anti-wear agent and graphene quantum dot compound modified additive, it successfully solves the technical problems of existing lubricating oils in corrosive flue gas environments, such as poor corrosion resistance, easy contamination, easy emulsification and short service life, achieving unexpected technical results.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lubricating oil technology, and in particular to a graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments and its preparation method. Background Technology

[0002] In the production of polyvinyl chloride (PVC), flue gas recovery fans are key power equipment for ensuring production continuity and efficient exhaust gas treatment. These fans operate long-term in harsh environments characterized by high corrosivity, high pollution, and high humidity. The flue gas typically contains acidic hydrogen chloride (HCl) gas at a concentration of 50-100 ppm, unpolymerized PVC dust with a particle size of 5-15 μm, and condensate formed from steam heating and flue gas cooling. These multiple adverse factors collectively pose a serious threat to the fan's lubrication system.

[0003] Currently, the industry commonly uses total loss system oils such as Kunlun L-AN46 as the lubricating medium for this type of fan. These traditional lubricants possess basic lubrication and anti-wear properties under normal operating conditions, and are relatively inexpensive and easy to replace. However, their application in the specific operating conditions of PVC flue gas recovery fans presents significant technical drawbacks: First, they lack acid neutralization capabilities; HCl gas intrusion into the oil rapidly increases the oil's acid value (≥0.4 mg KOH / g after 150 hours of use), leading to bearing raceway corrosion and pitting. Second, they have poor anti-fouling properties and lack efficient dispersants, causing PVC dust to agglomerate in the oil, forming gel-like blockages that reduce oil fluidity by 30% and clog oil passages. Third, they have insufficient anti-emulsification properties; when condensate mixes in, it cannot be quickly separated, leading to oil emulsification and stratification, a sharp drop in lubricating film thickness, and high bearing temperatures. Finally, all these problems result in extremely short oil change intervals (only 200-250 hours), and frequent shutdowns not only increase maintenance costs but also severely impact production efficiency.

[0004] To address the aforementioned issues, some improved lubricant formulations for specific operating conditions have emerged in the existing technology. For example, Chinese invention patent CN113563946A discloses an environmentally friendly marine lubricant that enhances its acid neutralization capacity and anti-wear performance by introducing a high-alkalinity acid neutralizer (comprising a blend of organic and inorganic bases) and highly efficient anti-wear additives. This technology primarily targets marine diesel engines to address the acidic substances produced by the combustion of high-sulfur fuels. However, its formulation system is not optimized for high-concentration PVC dust pollution and condensate contamination, lacks efficient dispersion design for polar dust, and does not strengthen demulsification performance as a core indicator.

[0005] Furthermore, Chinese invention patent CN108359455A discloses a method for extracting graphene quantum dots and a lubricating oil modifier formulated therein, utilizing the abundant functional groups on the surface of coal-based graphene quantum dots to enhance the friction-reducing and anti-wear capabilities of lubricating oil. Although this technology has advantages in reducing the coefficient of friction, it mainly focuses on improving lubrication performance through nano-additives, without addressing system solutions for complex working conditions such as acid gas neutralization, dust dispersion, and demulsification. Therefore, it is difficult to directly apply it to the special environment of PVC flue gas recovery fans, where multiple pollutants coexist.

[0006] It is evident that there is currently a lack of a dedicated lubricant that can effectively address the problems of acid corrosion, PVC dust pollution, and moisture contamination. In particular, there is a lack of a lubricant solution for PVC flue gas recovery fans that offers a long service life and low maintenance costs.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] The purpose of this invention is to provide a graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments and its preparation method. This graphene-based energy-saving lubricating oil solves the technical problems of existing lubricating oils having poor corrosion resistance, easy contamination, easy emulsification, and short service life in corrosive flue gas environments.

[0009] In a first aspect, the present invention provides a graphene-based energy-saving lubricating oil specifically for fans in corrosive flue gas environments, comprising the following components in parts by weight: The composition includes 75-90 parts base oil, 2-6 parts extreme pressure anti-wear agent, 3-8 parts composite additive package, 1-5 parts graphene quantum dot compound modified additive, 1-3 parts detergent dispersant, 0.5-1.5 parts demulsifier, 0.2-1 part acid neutralizer, 0.1-0.5 parts friction modifier, and 0.2-0.8 parts antifoaming agent.

[0010] This invention employs a specific ratio of components to synergistically address the core challenges of corrosive flue gas environments. Specifically, the acid neutralizer rapidly neutralizes acidic substances such as HCl that infiltrate the oil, maintaining its alkalinity and preventing metal corrosion at its source; the detergent-dispersant efficiently suspends and disperses PVC dust and carbon particles, preventing their aggregation and deposition, thus maintaining unobstructed oil passages and a clean system; the deemulsifier ensures rapid oil-water separation, preventing emulsions from damaging the lubricating film; and combined with high-performance extreme pressure anti-wear agents and composite additives, the lubricating oil of this invention maintains excellent lubricity, stability, and an extended oil change interval even under extreme conditions of corrosiveness, high pollution, and high humidity.

[0011] More importantly, this invention introduces graphene quantum dot compound modified additives into graphene energy-saving lubricating oil. First, the graphene quantum dot compound modified additives, when used in combination with acid neutralizers, provide dual anti-corrosion effects. The abundant oxygen- and nitrogen-containing functional groups on the surface of graphene quantum dots can effectively adsorb and stabilize the polar products generated when the acid neutralizer neutralizes HCl, preventing their aggregation and deposition. Simultaneously, the physical barrier layer formed by the chemical inertness and layered structure of graphene quantum dots slows down the diffusion rate of HCl to the metal surface, allowing the acid neutralizer to be "consumed in stages," thus extending the effective neutralization time under the same alkalinity reserve. Second, graphene quantum dots and detergent dispersants can form an "anchoring-dispersion" mode. That is, graphene quantum dots, due to their nanoscale size, preferentially adsorb onto the surface of PVC particles, changing their surface polarity, making it easier for the dispersant to anchor and encapsulate dust, forming a new mechanism of "nanoparticle-assisted dispersion." Thus, this invention effectively solves the two core contradictions of "acidic corrosion" and "dust pollution" in corrosive flue gas environments. The lubricating oil has an alkalinity reserve of ≥2.0 mg KOH / g, which can effectively neutralize HCl gas and can withstand PVC dust of more than 1.0% without agglomeration. Finally, the extreme pressure anti-wear agent and graphene quantum dots can form an "instant-reserve" dual-mode lubrication. Specifically, graphene quantum dots, due to their nanoscale size, preferentially enter the microscopic wear region of the friction pair, forming a physical adsorption film, filling microscopic defects, achieving self-repair function, and greatly reducing the coefficient of friction. Under high temperature and high load, the active sulfur generated by the decomposition of the extreme pressure anti-wear agent reacts with the metal to form a chemical reaction film. At the same time, graphene quantum dots can act as "nucleation sites" to induce a more uniform and denser growth of the reaction film, thereby giving the lubricating oil superior anti-wear performance and an ultra-long oil change interval.

[0012] As a preferred embodiment of this technical solution, the graphene quantum dot composite modifier comprises the following components in parts by weight: The composition includes 30-50 parts graphene quantum dots, 15-30 parts polytetrafluoroethylene nanospheres, 10-25 parts hexagonal boron nitride nanosheets, 5-15 parts serpentine powder, and 2-8 parts dispersant and stabilizer.

[0013] Graphene quantum dots possess excellent mechanical strength and chemical inertness. Synergistically with hexagonal boron nitride, their complementary two-dimensional structures allow for the formation of a denser and more stable lubricating film at the friction interface. Polytetrafluoroethylene (PTFE) nanospheres exhibit excellent chemical inertness and thermal stability. Their soft lubricating properties complement the hard reinforcing properties of graphene quantum dots, forming a composite lubricating film that combines softness and hardness. Serpentine powder primarily serves as a wear self-healing agent. Under frictional heat and pressure, serpentine decomposes and undergoes a tribochemical reaction, generating ceramic protective layers such as iron silicates and iron-magnesium silicates. Therefore, its interaction with graphene quantum dots forms a "physical-chemical" bilayer self-healing system. Dispersing stabilizers mainly inhibit the re-agglomeration of nanoparticles through steric hindrance or electrostatic repulsion, preventing additives from settling and stratifying during long-term storage, thus ensuring batch consistency during use.

[0014] As a preferred embodiment of this technical solution, the base oil includes any one or more of polyalphaolefin synthetic oil, alkylnaphthalene synthetic oil, Group III hydrogenated mineral oil, and Group II+ hydrogenated mineral oil.

[0015] As a preferred embodiment of this technical solution, the acid neutralizing agent is a sulfonate with a total base value greater than 150 mg KOH / g, and is preferably high-base-value calcium sulfonate, magnesium sulfonate, or a mixture of both. Examples include T106A and T106B from Jinzhou Xinxing and RF1106 from Ruifeng New Materials.

[0016] In addition to their high acid neutralization performance, the high-alkalinity sulfonates selected in this invention also help prevent the agglomeration of small particles through the two-electron effect and the formation of an adsorption film, thereby assisting in the dispersion of PVC dust.

[0017] As a preferred embodiment of this technical solution, the cleaning and dispersing agent is a polyisobutylene succinimide dispersant, and more preferably any one of monosuccinimide, bissuccinimide, and high molecular weight succinimide. Examples include Jinzhou Xinxing T151 (monosuccinimide), Jinzhou Xinxing T154 (bissuccinimide), and Jinzhou Xinxing T161 (high molecular weight succinimide).

[0018] Polyisobutylene succinimide dispersants consist of relatively long polyisobutylene lipophilic chains (molecular weight approximately 1000-2300) and polar succinimide groups. This molecular structure can form a thick steric hindrance layer on the surface of PVC dust and graphene quantum dots, effectively preventing particle agglomeration and stably suspending contaminants in the oil phase. Simultaneously, its polar groups can form a strong adsorption effect with the oxygen-containing functional groups on the surface of graphene quantum dots, promoting the stable dispersion of nanomaterials in oil. Furthermore, when combined with high-alkalinity sulfonates, it can form mixed micelles, further enhancing the system's detergency and acid neutralization capacity.

[0019] As a preferred embodiment of this technical solution, the demulsifier is a polyether-based demulsifier, and more preferably one or more of EO / PO block copolymers, multi-monomer copolyethers, and fatty acid polyoxyethylene esters. Examples include BASF Basorol PDB 5951, T-1001, and Jinzhou Shengda DL-32.

[0020] As a preferred embodiment of this technical solution, the extreme pressure anti-wear agent is a sulfurized olefin-based extreme pressure anti-wear agent, preferably one or more of sulfurized isobutylene and dialkyl pentasulfides. Examples include Lanzhou Lubricating Oil Additive T321, Luoyang Xipeng XP440, and Luoyang Xipeng XP43.

[0021] Sulfated olefin-based extreme pressure anti-wear agents have high sulfur content and highly active sulfur, enabling them to form physically or chemically adsorbed films on metal surfaces. More importantly, with the synergy of graphene quantum dots in this invention, the sulfurized olefin-based extreme pressure anti-wear agent can form a dual-mode lubrication system of "instantaneous + reserve" with graphene quantum dot-modified additives. Graphene quantum dots provide a physically adsorbed film in the medium and low temperature range, while the extreme pressure anti-wear agent takes over to generate a chemically reacted film under high temperature and high load conditions, thereby achieving full-condition coverage.

[0022] As a preferred embodiment of this technical solution, the friction modifier is an organic molybdenum composite agent, and is preferably one or more of molybdenum dialkyl dithiocarbamate, molybdenum dialkyl dithiophosphate, and molybdenum amine ester, wherein molybdenum dialkyl dithiocarbamate includes Japanese ADEKA SAKURA-LUBE 525, Pacific Union POUPC1002, and Runxian Antifrac 8902, etc.

[0023] More preferably, the extreme pressure anti-wear agent is Lanzhou Lubricating Oil Additive T321, and the friction modifier is molybdenum dialkyldithiocarbamate. The MoS2 film formed at the friction interface and the FeS chemical reaction film formed by T321 can form a synergistic lubrication layer.

[0024] As a preferred embodiment of this technical solution, the composite additive package is a multifunctional composite agent for gear oil, and preferably one or more of general-purpose gear oil composite agents and industrial gear oil composite agents. Examples include Afton HiTEC® 3339, Afton HiTEC® 3500, BRB Petrolad® 336, Jinzhou Shengda SR-4201, Jinzhou Shengda SR-4202, and Jinzhou Kangtai KT55003, etc.

[0025] As a preferred embodiment of this technical solution, the antifoaming agent is an organosilicon or composite antifoaming agent, and more preferably one or more of the following: non-silicone acrylate antifoaming agents, organosilicon and polymer composite antifoaming agents, and polyether-modified silicone oil antifoaming agents. Examples include Jinzhou Xinxing T-903, Jinzhou Shengda T903, and Simin Oil FoamQuer 9717H.

[0026] As a preferred embodiment of this technical solution, the preparation method of the graphene quantum dot composite modified additive includes the following steps: Under inert gas protection, graphene quantum dots and hexagonal boron nitride were added to a ball mill for doping modification to obtain GQDs-BN composite. Polytetrafluoroethylene nanospheres and a portion of base oil were pre-dispersed by ultrasound to obtain a PTFE pre-dispersion. A graphene quantum dot composite modified additive was obtained by mixing GQDs-BN composite, PTFE predispersant, serpentine powder and dispersant stabilizer.

[0027] In the preparation method of the graphene quantum dot composite modified additive of the present invention, firstly, under the protection of an inert gas, graphene quantum dots and hexagonal boron nitride are added to a ball mill for doping modification. During the ball milling process, the mechanochemical action causes the graphene quantum dots and hexagonal boron nitride (BN) nanosheets to form an interfacial bond, forming a heterostructure. This composite structure is more stable and has a more significant synergistic effect than simple physical mixing. At the same time, PTFE nanospheres have a large specific surface area and low surface energy, and are prone to agglomeration. By pre-dispersing with ultrasound and a portion of the base oil, the agglomerates can be effectively opened, ensuring their uniform distribution in the final additive. Further, the GQDs-BN composite, PTFE pre-dispersion liquid, serpentine powder, and dispersing stabilizer are mixed to form a synergistic system. Finally, by vacuum drying and air jet milling, moisture is removed and the particles are further refined to ≤10 nm to ensure nanoscale dispersion, thus obtaining the graphene quantum dot composite modified additive.

[0028] Secondly, this invention also discloses a method for preparing the above-mentioned graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments, specifically including the following steps: S1. Add the base oil to the mixing vessel, heat and stir to 50-80℃; S2. Add extreme pressure anti-wear agent, composite additive package, detergent dispersant and acid neutralizer to base oil in sequence, and stir at 500-2000 rpm for 20-40 min; S3. Continue to add graphene quantum dot composite modifiers and circulate them at a shear rate of 15000-30000 r / min for 2-4 hours. S4. Continue to add demulsifier, antifoaming agent and friction modifier, reduce the speed to 100-500 rpm, and stir for 10-20 min; S5. Cool the mixture to 40-60℃ and homogenize it using a high-shear homogenizer for 0.5-2.5 h. S6. After vacuum degassing and filtration, a graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments is obtained.

[0029] In the preparation method of the graphene energy-saving lubricating oil of this invention, the order of addition and mixing conditions are arranged according to the physicochemical properties of each functional component. Specifically, considering the tendency of graphene quantum dot compound modified additives to agglomerate, a high shear rate is applied for cyclic processing to achieve nanoscale uniform dispersion in the oil phase. Simultaneously, shear-sensitive components such as antiemulsifiers and antifoaming agents are added later and mixed gently at low speeds to avoid structural damage. Finally, through cyclic homogenization and vacuum degassing, a high-stability, high-cleanliness finished lubricating oil is obtained.

[0030] The graphene-based energy-saving lubricating oil of the present invention has at least the following beneficial effects: 1. The graphene-based energy-saving lubricating oil of this invention comprises a graphene quantum dot composite modified additive and an acid neutralizer. The salts and water generated when the acid neutralizer neutralizes HCl typically disrupt the dispersion stability of ordinary nanomaterials. However, the abundant oxygen- and nitrogen-containing functional groups on the surface of the graphene quantum dots in the graphene quantum dot composite modified additive used in this invention can effectively adsorb and stabilize the polar products generated during the neutralization reaction, preventing their aggregation and deposition. Furthermore, due to the extremely high specific surface area of ​​graphene quantum dots, their functional group density is sufficient to maintain their effectiveness throughout the oil change cycle. Simultaneously, the physical barrier layer formed by the graphene quantum dots slows down the diffusion rate of HCl to the metal surface, allowing the acid neutralizer to be "gradually consumed." After accelerated HCl testing, the rust level reaches the optimal level 0, and the effective neutralization time is extended under the same alkalinity reserve.

[0031] 2. The cleaning and dispersing agent in the graphene energy-saving lubricating oil of this invention, combined with the graphene quantum dot modified additive, forms an "anchoring-dispersion" mode. Specifically, the graphene quantum dots, due to their nanoscale size, preferentially adsorb onto the surface of PVC particles, changing their surface polarity, making it easier for the dispersant to anchor and encapsulate dust, thus forming a new mechanism of "nanoparticle-assisted dispersion." Therefore, this invention effectively solves the two core contradictions of "acid corrosion" and "dust pollution" in corrosive flue gas environments. The lubricating oil has an alkalinity reserve of ≥2.0 mg KOH / g, which can effectively neutralize HCl gas, while tolerating PVC dust of more than 1.0% without agglomeration.

[0032] 3. The graphene-energy-saving lubricating oil of this invention, with its extreme pressure anti-wear agent and graphene quantum dot composite modified additive, can form a dual-mode lubrication system of "instantaneous-reservoir". Specifically, graphene quantum dots, due to their nanoscale size, preferentially enter the microscopic wear region of the friction pair, forming a physical adsorption film (instantaneous lubrication). Under high temperature and high load, the active sulfur generated by the decomposition of the extreme pressure anti-wear agent reacts with the metal to form a chemical reaction film. At the same time, graphene quantum dots can act as "nucleation sites" to induce a more uniform and denser growth of the reaction film. Based on mineral oil, it achieves anti-wear and energy-saving performance close to or exceeding that of synthetic oil, reducing the coefficient of friction to below 0.06, significantly extending the service life of equipment in corrosive environments, and extending the oil change cycle from 200-250 hours in the prior art to more than 8000 hours, far exceeding existing products.

[0033] 4. The introduction of demulsifier into the graphene energy-saving lubricating oil of this invention greatly improves the demulsibility of the lubricating oil. The water separation time at 54°C is ≤7 minutes, which can quickly separate the intruding condensate and ensure the stability of the oil film. Detailed Implementation

[0034] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0035] It should be noted that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the exemplary implementations according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this description, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0036] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] Example 1 This embodiment provides a method for preparing a graphene quantum dot composite modified additive, including the following steps: (1) Under nitrogen protection, 40 parts of graphene quantum dots and 20 parts of hexagonal boron nitride were added to a planetary ball mill, and 5 parts of silane coupling agent were added at the same time. The mixture was ball-milled at 350 r / min for 1.5 hours to dope and modify the material, and the GQDs-BN composite was obtained. (2) Add 25 parts of polytetrafluoroethylene nanospheres and 50 parts of base oil to an ultrasonic homogenizer and ultrasonically treat for 40 min at 1800W power and 40-45℃ to obtain PTFE predispersant. (3) Add GQDs-BN composite, PTFE pre-dispersion liquid, 10 parts of serpentine powder and 5 parts of dispersant stabilizer to a high-speed dispersion vessel, stir and mix at 6000 r / min for 2 hours, and then vacuum dry and air-jet pulverize to obtain graphene quantum dot composite modified additive with an average particle size ≤10 nm.

[0038] Example 2 This embodiment provides a method for preparing a graphene quantum dot composite modified additive, including the following steps: (1) Under nitrogen protection, 30 parts of graphene quantum dots and 10 parts of hexagonal boron nitride were added to a planetary ball mill, and 5 parts of silane coupling agent were added at the same time. The mixture was ball-milled at 350 r / min for 1.5 hours to dope and modify the material, and GQDs-BN composite was obtained. (2) Add 15 parts of polytetrafluoroethylene nanospheres and 30 parts of base oil to an ultrasonic homogenizer and ultrasonically treat for 40 min at 1800W power and 40-45℃ to obtain PTFE predispersant. (3) Add GQDs-BN composite, PTFE pre-dispersion liquid, 5 parts of serpentine powder and 2 parts of dispersant stabilizer to a high-speed dispersion vessel, stir and mix at 6000 r / min for 2 hours, and then vacuum dry and air-jet pulverize to obtain graphene quantum dot composite modified additive with an average particle size ≤10 nm.

[0039] Example 3 This embodiment provides a method for preparing a graphene quantum dot composite modified additive, including the following steps: (1) Under nitrogen protection, 50 parts of graphene quantum dots and 25 parts of hexagonal boron nitride were added to a planetary ball mill, and 10 parts of silane coupling agent were added at the same time. The mixture was ball-milled at 350 r / min for 1.5 hours to dope and modify the material, and the GQDs-BN composite was obtained. (2) Add 30 parts of polytetrafluoroethylene nanospheres and 60 parts of base oil to an ultrasonic homogenizer and ultrasonically treat for 40 min at 1800W power and 40-45℃ to obtain PTFE predispersant. (3) Add GQDs-BN composite, PTFE pre-dispersion liquid, 15 parts of serpentine powder and 8 parts of dispersant stabilizer to a high-speed dispersion vessel, stir and mix at 6000 r / min for 2 hours, and then vacuum dry and air-jet pulverize to obtain graphene quantum dot composite modified additive with an average particle size ≤10 nm.

[0040] Example 4 This embodiment provides a graphene-based energy-saving lubricating oil and its preparation method.

[0041] In this embodiment, the graphene energy-saving lubricating oil comprises the following components in parts by weight: The base oil is a mixture of PAO 40 and alkyl naphthalene (mass ratio 7:3), 83.5 parts. The extreme pressure anti-wear agent selected is 5.5 parts of Lanzhou Lubricating Oil Additive T321. The compound additive package contains 6 parts of Afton HiTEC® 3339. Graphene quantum dot compound modified additive (Example 1) 3 parts, Two parts of Jinzhou Xinxing T-151 were selected as the cleaning and dispersing agent. The demulsifier used was 0.8 parts of BASF Basorol PDB 5951. The acid neutralizing agent used was 0.5 parts of Jinzhou Xinxing T106A with a TBN of ≈295 mg KOH / g. The friction modifier used was 0.2 parts of Pacific United POUPC1002. The antifoaming agent used was 0.5 parts of Jinzhou Xinxing T-903.

[0042] The preparation method of graphene energy-saving lubricating oil in this embodiment includes the following steps: S1. Add the base oil to a 304 stainless steel mixing vessel and heat it to 50-80℃ at 120r / min; S2. Add extreme pressure anti-wear agent, composite additive package, detergent dispersant and acid neutralizer to base oil in sequence, and stir at 500-2000 rpm for 20-40 min. S3. Continue to add graphene quantum dot composite modifiers, and turn on the high shear homogenizer to circulate the mixture at 15000-30000r / min for 2-4 hours. S4. Continue to add demulsifier, antifoaming agent and friction modifier, reduce the speed to 100-500 rpm, and stir for 10-20 min; S5. Cool the material to 40-60℃, pump it into an online high-shear homogenizer, and circulate it for 0.5-2.5 hours at a shear rate of 15000-20000r / min. S6. Degas under a vacuum of -0.098MPa for 20-30 minutes, then filter through a 1μm precision filter to obtain graphene energy-saving lubricating oil.

[0043] Example 5 This embodiment is basically the same as embodiment 4, except that: In this embodiment, the graphene energy-saving lubricating oil comprises the following components in parts by weight: The base oil used is 75 parts of Group III hydrogenated mineral oil. Extreme pressure anti-wear agent selected is 2 parts of Lanzhou lubricating oil additive T321. The compound additive package uses 3 parts of Jinzhou Shengda SR-4201. Graphene quantum dot compound modified additive (Example 2) 2 parts The cleaning and dispersing agent selected is 1 part of Jinzhou Xinxing T154. The demulsifier used was 0.5 parts of Jinzhou Shengda DL-32. One part of Jinzhou Xinxing T106B (TBN≈300mgKOH / g) was selected as the acid neutralizing agent. The friction modifier used was 0.5 parts of Runxian brand Antifrac 8902. The antifoaming agent used is FoamQuer 9717H oil, 0.2 parts.

[0044] Example 6 This embodiment is basically the same as embodiment 4, except that: In this embodiment, the graphene energy-saving lubricating oil comprises the following components in parts by weight: The base oil is selected from 90 parts of Group III hydrogenated mineral oil. Extreme pressure anti-wear agent selected: 5 parts of Luoyang Xipeng XP440. The compound additive package uses 8 parts of BRB Petrolad® 336. Graphene quantum dot compound modified additive (Example 3) 3 parts Two parts of Jinzhou Xinxing T151 were selected as the cleaning and dispersing agent. The demulsifier used was BASF Basorol PDB 5951, 1.0 part. The acid neutralizing agent used was 0.5 parts of Jinzhou Xinxing T106A with a TBN of ≈295 mg KOH / g. The friction modifier used was 0.5 parts of ADEKA SAKURA-LUBE 525 from Japan. The antifoaming agent used was 0.8 parts of Jinzhou Xinxing T-903.

[0045] Compare with Example 1 This comparative example is basically the same as Example 4, except that ordinary graphene nanosheets of the same weight are used instead of graphene quantum dot compound modifiers.

[0046] Specifically, in this comparative example, the lateral dimensions of ordinary graphene nanosheets are 0.5-5 μm and the thickness is 1-5 nm.

[0047] Compare with Example 2 This comparative example is basically the same as Example 4, except that the same weight proportion of ordinary calcium carbonate powder is used instead of the high-alkalinity sulfonate neutralizer Jinzhou Xinxing T106A.

[0048] Compare with Example 3 This comparative example is basically the same as Example 4, except that the same weight parts of Span60 (sorbitan monostearate) are used instead of Jinzhou Xinxing T-151 detergent dispersant.

[0049] Compare with Example 4 This comparative example is basically the same as Example 4, except that the same weight parts of sulfurized fat are used instead of T321 extreme pressure anti-wear agent.

[0050] The performance of the graphene energy-saving lubricating oils prepared in Example 4 and Comparative Examples 1-4 was tested under a simulated corrosive flue gas environment. The results are shown in Table 1 below.

[0051] (1) Acid neutralization capacity: The total base number (TBN) was tested according to ASTM D2896, and the accelerated corrosion test was used. 100 ppm HCl was added to the oil and stirred at 80°C for 150 hours to test the increase in acid number.

[0052] (2) Corrosion resistance: Copper sheet corrosion test (100℃, 3h) was conducted in accordance with ASTM D130, and a custom HCl vapor phase corrosion test (bearing steel specimen, 80℃, HCl concentration 100ppm, 72h) was conducted to observe the corrosion level.

[0053] (3) Anti-fouling properties: Add 1.5wt% of PVC dust (particle size 5-15μm) to the oil, stir at 60℃ for 200 hours, observe the changes in the appearance of the oil and test the rate of decrease in fluidity.

[0054] (4) Demulsibility: Refer to ASTM D1401 for water separation time at 54°C.

[0055] (5) Extreme pressure wear resistance: The maximum non-stick load (PB) and wear scar diameter were tested by four ball test according to ASTM D2783.

[0056] (6) Antioxidant properties: Oxidation stability is tested according to ASTM D2272 (RPVOT).

[0057] (7) Oil change cycle simulation: Based on comprehensive performance indicators and accelerated life test, the recommended oil change cycle under typical PVC flue gas environment is estimated.

[0058] Table 1. Performance test results of graphene-based energy-saving lubricating oils in Example 4 and Comparative Examples 1-4

[0059] As shown in Table 1, the graphene-based energy-saving lubricating oil prepared in Example 4 of this invention exhibits minimal increase in acid value after HCl accelerated testing, achieving the optimal rust grade of 0, indicating its excellent resistance to acid corrosion. Furthermore, this graphene-based energy-saving lubricating oil effectively suspends PVC dust, with an oil fluidity reduction rate of only 3%, far lower than that of Control Examples 1-4, demonstrating its excellent anti-fouling performance. Simultaneously, this graphene-based energy-saving lubricating oil also exhibits excellent extreme pressure anti-wear and oxidation resistance; its PB value (880N) and wear scar diameter (0.32mm) are significantly superior to the control examples, its RPVOT reaches 2800 minutes, and its oil change cycle exceeds 8000 hours. These data fully demonstrate that the graphene-based energy-saving lubricating oil provided by this invention has a significant long-life advantage in corrosive flue gas environments.

[0060] In contrast, Comparative Example 1, which used ordinary graphene nanosheets instead of the graphene quantum dot compound modifiers of this invention, showed that its acid value after HCl acceleration was 0.22 mg KOH / g, significantly higher than that of Example 4. The corrosion grade deteriorated from level 0 to level 1, the fluidity decreased by as much as 15%, and the PB value and wear scar diameter were inferior to those of Example 4. The oil change cycle was shortened to 3800 hours. This may be because the lateral size of ordinary graphene nanosheets (0.5-5 μm) is much larger than that of graphene quantum dots (1-10 nm), making them prone to agglomeration and sedimentation in oil. They cannot form a dense and continuous physical barrier layer, nor can they enter the microscopic wear zone of the nanoscale friction pair to exert a self-repair function. At the same time, their surface functional groups are scarce, making it impossible to effectively anchor dispersants and extreme pressure anti-wear agents. The synergistic effect with acid neutralizers and extreme pressure anti-wear agents is significantly weakened, and abrasive wear may even occur due to the formation of agglomerates.

[0061] In Comparative Example 2, ordinary calcium carbonate powder was used instead of the high-alkalinity sulfonate acid neutralizer of this invention. The results showed that after HCl acceleration, the acid value increased by as much as 0.48 mg KOH / g, the corrosion level worsened to level 2-3, and the oil change interval was shortened to 4500 hours. This may be because: calcium carbonate powder is an oil-insoluble solid particle, which cannot form the micelle structure unique to high-alkalinity sulfonates in the base oil. Most of it settles as solid particles, unable to fully contact the HCl that penetrates the oil, resulting in extremely low acid neutralization efficiency; simultaneously, it cannot form a synergistic anti-corrosion barrier with graphene quantum dots, and unreacted solid particles may deposit on the friction surface, affecting lubrication and causing abrasive wear.

[0062] In Comparative Example 3, ordinary Span60 was used instead of the monosuccinimide detergent dispersant Jinzhou Xinxing T151 of the present invention. The results showed that the initial TBN decreased from 3.5 mg KOH / g to 2.0 mg KOH / g, the acid value increased to 0.31 mg KOH / g after HCl acceleration, the fluidity decreased by as much as 18%, the water separation time was extended to 18 minutes, and the oil change cycle was shortened to 3500 hours. This may be because: Span60 is a small-molecule nonionic surfactant with a molecular weight of only about 431. Its short-chain structure cannot provide the steric hindrance effect of T151 (molecular weight about 1000) long-chain polyisobutylene, making it difficult to stably suspend PVC dust and graphene quantum dots; its molecular structure lacks active groups (such as succinimide groups) that can form strong interactions with the surface functional groups of graphene quantum dots, resulting in uneven dispersion and aggregation of graphene quantum dots in the oil phase; at the same time, Span60 has high surface activity, which will excessively reduce the oil-water interfacial tension and severely deteriorate the demulsification performance; in addition, Span60 cannot effectively assist in the dispersion of T106A high-base-value sulfonate, causing some T106A to precipitate, which in turn reduces the total base value of the system and results in insufficient acid neutralization capacity.

[0063] In Comparative Example 4, using ordinary sulfurized grease instead of the sulfurized isobutylene extreme pressure anti-wear agent (T321) of this invention resulted in a decrease in the PB value from 880 N to 740 N, an increase in the wear scar diameter from 0.32 mm to 0.46 mm, a decrease in the RPVOT value from 2800 minutes to 2500 minutes, and a reduction in the oil change interval to 5000 hours. This may be because sulfurized grease has poor thermal stability, with active sulfur being released prematurely at 100-120°C. The "instant + reserve" dual-mode lubrication required by this invention necessitates that the active sulfur release temperature of the extreme pressure anti-wear agent match the timing of frictional heat generation, so as to form a chemical reaction film under high temperature and high load conditions when the graphene quantum dot physical adsorption film is about to fail. The premature decomposition of sulfurized grease leads to insufficient protection in the high-temperature zone, and its low sulfur content also results in insufficient thickness and strength of the formed chemical reaction film. Furthermore, its decomposition products may catalyze oil oxidation, further shortening its service life.

[0064] Compared with Comparative Examples 1-4, it is evident that using ordinary graphene nanosheets, calcium carbonate powder, small molecule surfactants, sulfurized fats, or commercially available synthetic oils cannot simultaneously achieve the comprehensive performance of this invention in terms of corrosion resistance, pollution resistance, wear resistance, and long service life. This fully demonstrates that the technical effect of this invention originates from the specific combination and synergistic effect of graphene quantum dot compound modified additives with components such as acid neutralizers, detergents and dispersants, and extreme pressure anti-wear agents, rather than a simple summation of the effects of individual components.

[0065] In summary, this invention, through targeted component design, successfully solves the technical problems of existing lubricating oils, such as poor corrosion resistance, easy contamination, easy emulsification, and short service life in corrosive flue gas environments, and achieves significant technical results.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A graphene-based energy-saving lubricating oil specifically for fans in corrosive flue gas environments, characterized in that, The components include the following parts by weight: The composition includes 75-90 parts base oil, 2-6 parts extreme pressure anti-wear agent, 3-8 parts composite additive package, 1-5 parts graphene quantum dot compound modified additive, 1-3 parts detergent dispersant, 0.5-1.5 parts demulsifier, 0.2-1 part acid neutralizer, 0.1-0.5 parts friction modifier, and 0.2-0.8 parts antifoaming agent.

2. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The graphene quantum dot composite modified additive comprises the following components in parts by weight: The composition includes 30-50 parts graphene quantum dots, 15-30 parts polytetrafluoroethylene nanospheres, 10-25 parts hexagonal boron nitride nanosheets, 5-15 parts serpentine powder, and 2-8 parts dispersant and stabilizer.

3. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The base oil includes any one or more of polyalpha-olefin synthetic oil, alkylnaphthalene synthetic oil, Group III hydrogenated mineral oil, and Group II+ hydrogenated mineral oil; The acid neutralizing agent is a sulfonate with a total base value greater than 150 mg KOH / g.

4. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The cleaning and dispersing agent is a polyisobutylene succinimide dispersant.

5. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The deemulsifier is a polyether-based deemulsifier.

6. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The extreme pressure anti-wear agent is a sulfurized olefin-based extreme pressure anti-wear agent; The friction modifier is an organic molybdenum composite agent.

7. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The compound additive package is a multifunctional compound for gear oil.

8. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The antifoaming agent is an organosilicon-based or composite antifoaming agent.

9. The graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments according to claim 1, characterized in that, The preparation method of the graphene quantum dot composite modified additive includes the following steps: Under inert gas protection, graphene quantum dots and hexagonal boron nitride were added to a ball mill for doping modification to obtain GQDs-BN composite. Polytetrafluoroethylene nanospheres and a portion of base oil were pre-dispersed by ultrasound to obtain a PTFE pre-dispersion. A graphene quantum dot composite modified additive was obtained by mixing GQDs-BN composite, PTFE predispersant, serpentine powder and dispersant stabilizer.

10. The preparation method of the graphene energy-saving lubricating oil for fans in corrosive flue gas environments according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Add the base oil to the mixing vessel, heat and stir to 50-80℃; S2. Add extreme pressure anti-wear agent, composite additive package, detergent dispersant and acid neutralizer to base oil in sequence, and stir at 500-2000 rpm for 20-40 min; S3. Continue to add graphene quantum dot composite modifiers and cycle the mixture for 2-4 hours at a shear rate of 15000-30000 r / min. S4. Continue to add demulsifier, antifoaming agent and friction modifier, reduce the speed to 100-500 rpm, and stir for 10-20 minutes; S5. Cool the mixture to 40-60℃ and homogenize it using a high-shear homogenizer for 0.5-2.5 h. S6. After vacuum degassing and filtration, a graphene-based energy-saving lubricating oil for fans in corrosive flue gas environments is obtained.

Citation Information

Patent Citations

  • Method for extracting graphene quantum dots and lubricating oil modified additive prepared therefrom

    CN108359455A

  • Environment-friendly marine lubricating oil

    CN113563946A